Application of granulated copper slag in massive concrete under saline soil environment. (10th January 2021) - Zhou, Yuqi; Liu, Weiwei
Highlights: The cement blended with GCS can effectively reduce the hydration heat. Utilizing GCS to replace cement can improve the workability while reducing the yield stress. The concrete sample containing GCS can reduce the adiabatic temperature rise. The GCS has great potential as an SCM for massive concrete in the saline-soil environment. Abstract: The present study aimed to utilize granulated copper slag (GCS) as a mineral admixture for massive concrete in the saline-soil environment, then analyze the feasibility through the experiment. A contrastive analysis was conducted on the hydration heat in paste mixtures with a partial replacement of Ordinary Portland cement (OPC) by GCS and FA at different temperatures (25 °C and 50 °C). Results showed that the properties of cement blended with GCS were similar to that of FA, which can effectively reduce the hydration heat. The GCS influence on the fluidity, rheological performance, compressive strength, and chloride permeability of concrete was investigated. Results showed that utilizing GCS to replace cement can improve workability while reducing the yield stress, plastic viscosity, mechanical strength, and chloride permeability of concrete. By adjusting the w/b ratio and the GCS amount, three groups of concrete samples (C-0.40, G35-0.35, G40-0.32) with similar workability, compressive strength, and chloride permeability were selected for adiabatic temperature rise testing. A detailed analysis was conducted on the compressive strength, splitting tensile strength, chloride ion permeability, and sulfate attack resistance of concrete under the temperature match curing (TMC) condition. Results showed that the concrete sample containing GCS can reduce the adiabatic temperature rise, while slightly increasing the compressive strength, splitting tensile strength, chloride permeability, and sulfate attack resistance. The present study provided a theoretical basis for the application of GCS to the massive concrete.